The Influence of Health Promotion Strategies and Youth Empowerment on Pregnancy Prevention through Digital Systems - Isabelita Madeira Soare; Marce Petronela Nelci Bere; Arina Chusnatayaini (Master of Public Health Program Universitas STRADA Indonesia, 2024)
The aim of this research is to examine the influence of health promotion strategies and youth empowerment on pregnancy prevention through digital systems. This research design uses a systematic review, namely library research that examines critical quality journals, which have been filtered using inclusion criteria and uses several Google Scholar, Pubmed, Science Direct and Research Gate databases as literature in this research. A search for 2017-2024 articles shows 1,440 results by keyword influence digital system in health promotion strategies and youth empowerment for pregnancy prevention, which was filtered into 23 journals according to themes and analyzed. The research results show that the influence of health promotion strategies and youth empowerment in preventing pregnancy through digital systems can be done by 1) utilization Social media is a technical tool that allows a good communication process to be carried out with adolescence in providing information related to youth health and empowerment. 2) Create a national online portal that provides access to various public services related to youth health and empowerment. 3) The impact of the involvement of health media via the internet is able to improve health communication in the future and this information or stimulus will trigger a person's response to preventing teenage pregnancy. 4) Adolescent health information via digital media has an influence on adolescent attitude patterns, but supervision and monitoring is needed assistance by parents, teachers and peers who understand adolescent health. 5) The use of digital systems can also be a strategy that can be used by health workers, including nurses, to improve services and develop health promotion media, especially for adolescence.